Collaborating with mammographers to address their work-related musculoskeletal discomfort. Issue 10 (2nd October 2016) - Sommerich, Carolyn M.; Lavender, Steven A.; Evans, Kevin D.; Sanders, Elizabeth; Joines, Sharon; Lamar, Sabrina; Radin Umar, Radin Zaid; Yen, Wei-Ting; Park, SangHyun
Abstract: Mammographers are an understudied group of health care workers, yet the prevalence of musculoskeletal (MSK) symptoms in mammographers appears to be elevated, similar to many occupations in health care. In this study, we used a participatory approach to identify needs and opportunities for developing interventions to reduce mammographers' exposures to risk factors that lead to the development of MSK symptoms. In this paper, we present a number of those needs and several intervention concepts along with evaluations of those concepts from experienced mammographers. We include findings from a preliminary field test of a novel intervention concept to reduce the need to adopt awkward postures while positioning patients for a screening or diagnostic mammogram. Practitioner Summary: This paper discusses needs, opportunities and methods for working with mammographers in order to develop interventions to reduce their exposure to risk factors for work-related musculoskeletal discomfort. Results from a field test of a novel intervention to reduce mammographers' awkward work postures while positioning patients are presented.